Blood Transfusion and Postoperative Infection in Spine Surgery: A Systematic Review. Issue 2 (April 2018) - Fisahn, Christian; Schmidt, Cameron; Schroeder, Josh E.; Vialle, Emiliano; Lieberman, Isador H.; Dettori, Joseph R.; Schildhauer, Thomas A.
Study Design: Systematic review. Objectives: Allogeneic blood transfusion-related immunomodulation may relatively suppress the immune system, heightening the risk of infection following spine surgery. This systematic review seeks to determine whether allogeneic blood transfusion increases the risk of postoperative infection and whether there are any factors that modify this association. Methods: PubMed, Cochrane Central Register of Controlled Trials, and reference lists from included studies were searched from inception to April 20, 2017 to identify studies examining the risk of infection following allogeneic blood transfusion in adult patients receiving surgery for degenerative spine disease. Results: Eleven retrospective cohort or case-control studies, involving 8428 transfusion patients and 43 242 nontransfusion patients, were identified as meeting the inclusion criteria. Regarding surgical site infection (SSI), the results were mixed with roughly half reporting a significant association. There was an association between allogeneic transfusion and urinary tract infection (UTI) and any infection, but not respiratory tract infection. There was no statistical modifying effect of lumbar versus thoracic surgery on the association of allogeneic transfusion and SSI, though subgroup analyses in 3 of 4 studies reported a statistical association between transfusion and postoperative infections, including SSI, UTI, and any infection within the lumbar spine. Conclusions: This systematic review failed to find a consistent association between allogeneic transfusion and postoperative infection in spine surgery patients. However, these studies were all retrospective with a high or moderately high risk of bias. To properly examine this association an observational prospective study of sufficient power, estimated as 2400 patients, is required.